SOCIAL CAPITAL AS A FACTOR OF TOURISM DEVELOPMENT IN RURAL AREAS - Kosmaczewska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2009)
The objective of this article is to present the theoretical role of social capital (analyzing its positive aspect only) as endogen resources of local, rural community in view of the development of tourism in rural areas. The analyses were based on the literature on the said issues and then verified by means of the case study method (commune of Wijewo, commune of Kobyla Góra). A map of social capital in the communes of the province of Wielkopolska was drawn up using the method of the development pattern of Z. Hellwig (on the basis of the available statistical data) in order to determine the importance of human resources as a factor of the development of tourism in rural areas, this was followed by an attempt to determine the tourism function of rural areas (Baretje-Defert index of tourist function).and a hypothetical ponderings giving rise to conclusions on the synergy of the analyzed phenomena. The obtained results allowed to determine not only the social capital of the communities in the analyzed administrative units in general but also allowed for the examination of two different types of human activities making up two different types of societies. The analysis, carried out in this article, shows that the development of the tourism function is only possible in those rural areas where the inhabitants and the administrative bodies can so manage the resources they have at their disposal that, via cooperation and mutual trust, they can meet individual and collective objectives within informal networks and non-governmental organizations, increasing access of all the inhabitants of the commune to respective resources. Thus, the more coherent and diversified the offered product, the more complementary the services rendered by respective inhabitants, the greater the chance for successful development of tourism. The article poses a hypothesis that not only the social capital affect the development of tourism in rural areas but also the development of the tourism functions positively affects the social capital.